Metabolic modulation as a common adaptive mechanism in patients with different subtypes of aortic valve stenosis. (3rd October 2022) - Bengel, P; Beuthner, B E; Topci, R; Pietzner, M; Hasenfuss, G; Toischer, K; Schnelle, M
Abstract: Background: Aortic valve stenosis (AS) is a rapidly growing global health problem due to aging and population growth. If treatment by aortic valve replacement (AVR) is delayed, this leads to poor recovery of cardiac function and marked increase of mortality. In conditions of AS or heart failure a cardiac remodelling occurs including a change in cardiac substrate utilization. However, it is difficult to determine the stage of AS-induced cardiac remodelling and therefore the reversibility of this changes after AVR. As cardiac metabolism might be therapeutic target for patients not recovering after valve replacement a better understanding of the metabolic remodelling in different AS subtypes is necessary. Metabolomics constitute a potent screening tool for defining changes in global and cardiac-specific metabolism in cardiovascular disease. Methods/Results: Serum metabolomic profiling for 1293 metabolites was performed in serum samples of 40 AS-patients and 10 healthy controls using Ultrahigh Performance Liquid Chromatography-Tandem Mass Spectroscopy. AS-patients were divided in four groups (10 patients/group) with respect to ejection fraction (EF, normal/reduced) and aortic valve gradient (> or <40 mmHg). Principal component analysis revealed a clear difference of metabolic profiles in AS-patients vs controls. However, less separation between AS-subtypes could be detected. A Random Forest Analysis comparing all AS-patients to healthy controls resulted in a predictive accuracy of 94%. In AS-patients we observed an increase of acyl carnitines compared to control indicating an alteration of myocardial free fatty acid oxidation. Moreover, we detected a higher ketone body concentrations in AS-patients that could serve as an alternative fuel source for the heart. Interestingly, no differences between the AS subgroups could be detected indicating that changes occur independently from EF and AS-gradient. Additionally, several compounds involved in nitrogen balance were increased in AS-patients while numerous amino acids were decreased, possibly also due to alternative energy production. Increased circulating heme catabolites have been associated with heart failure. Here, we found increased heme catabolites only in patients with low EF and high-gradient with unclear significance. Conclusion: In summary, our study indicates a shift of cardiac substrate utilization in patients with AS from free fatty acid oxidation to alternative substrates like ketone bodies and amino acids. As no differences between AS subtypes were observed, this metabolic remodelling may occur as an adaptive mechanism independent from EF and AS-gradient in patients with severe AS. Since our study was conducted by an unspecific approach with a small sample size, further investigation is necessary for a better understanding of the specific myocardial metabolic changes in AS patients. Funding Acknowledgement: Type of funding sources: None.